Perancangan Sistem Informasi Manajemen Stok Barang Berbasis Web Meggunakan Model Waterfall Pada Toko Dhanisa Mandiri Jaya - Fazzil Alfis Ramadhan; Muhammad Isa Amsory; Muhammad Ikhsan; Wasis Haryono (Asosiasi Profesi Telekomunikasi dan Informatika Indonesia, 2025)
Manual stock management systems are still commonly used in electrical equipment sales businesses, often leading to problems such as inaccurate data recording, delayed reporting, and potential data loss. To overcome these issues, a web-based inventory management information system was developed to automate the recording of incoming goods, outgoing goods, damaged items, and lost items. A case study was conducted at Toko Dhanisa Mandiri Jaya, which previously relied on manual bookkeeping using physical logs. The system was developed using the Waterfall method, involving stages such as requirements analysis, system design, implementation, testing, and maintenance. Data collection was carried out through observation, interviews, and literature review. The system includes key features such as inventory data management, transaction processing, reporting, and user management. The implementation results indicate improved operational efficiency, reduced recording errors, and the availability of real-time inventory data to support managerial decision-making. This system is expected to help the store modernize its business processes with better accuracy and control.